Platelet reactive alloantibodies responsible for immune thrombocytopenia in Malay population (Faculty of Medicine Universitas Indonesia, 2014)
Background: Alloantibodies against human platelet alloantigens (HPAs) are responsible for the development of platelet transfusion refractoriness (PTR) in patients receiving random platelets and bleeding disorder in babies with fetal neonatal alloimmune thrombocytopenia (FNAIT). Recently, our results based on the analysis of the allelic distribution of HPAs indicated that immunization may occur among Malay. In this study, we sought to analyze the frequencies of platelet reactive alloantibodies responsible for FNAIT and PTR in Malaysia.Methods: Sera from suspected FNAIT (n = 295) and PTR (n = 74) were collected in five years period (2008-2013) and tested for the presence of platelet reactive antibodies by the use of antigen capture assay. Results: In 5/74 (5.41%) platelet specific antibodies against HPA-2b (n = 1), HPA-5a (n = 1), HPA-5b (n = 1), HPA-15b (n = 2) could be identified in our PTR cohort. In FNAIT cohort, platelet specific alloantibodies could be detected in 18 sera (6.10%) consisting anti-HPA-1a (n = 1), anti-HPA-3a (n = 3), anti-HPA-5a (n = 6), anti-HPA-5b (n = 6), anti-HPA-15a (n = 1), and anti-HPA-15b (n = 1). Conclusion: Our study indicates that anti-HPA-3, -HPA-5 and -HPA-15 antibodies seems to be the most platelet specific antibodies involved in FNAIT and PTR cases in Malaysian population. Since similar HPA allelic distribution among Malaysian and Indonesian populations have been observed, immunization against these three HPA systems are expected to be the most potential risk of alloimmune mediated platelet disorders in Indonesia.